A resin composition and a prepreg and laminate made using the same

By using a resin composition including a prepolymer, a thermosetting resin and an inorganic filler, the problem of difficult to achieve both heat resistance and low thermal expansion coefficient in the prior art is solved, and better overall performance and better processability are achieved.

CN119752197APending Publication Date: 2025-04-04SHENGYI TECH SUZHOU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411726410.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to have excellent heat resistance and low thermal expansion coefficient in high-density installation and high multilayer laminated plates, and there are problems such as weak bending resistance and poor material processability.

Method used

Using a resin composition, including a prepolymer, a thermosetting resin, an inorganic filler and a catalyst, the prepolymer is prepared by reacting in an organic solvent and combined with the thermosetting resin and an inorganic filler to form a semi-cured sheet and a laminate.

Benefits of technology

The heat resistance, peel strength, low dielectric properties, bending properties and low thermal expansion coefficient of the modified maleimide prepolymer are improved, the curing conditions are reduced, and the processability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_10
    Figure SMS_10
Patent Text Reader

Abstract

The invention discloses a resin composition and a prepreg and a laminate made by using the same. The resin composition comprises the following components by weight: 80 to 150 parts of a prepolymer; 5 to 100 parts of a thermosetting resin; and 10 to 400 parts of an inorganic filler. The prepolymer is obtained by reacting 30 to 70 parts of a maleimide resin, 5 to 25 parts of a difunctional vinylbenzene compound, 10 to 50 parts of an amino-modified silicone oil and 1 to 10 parts of an aminophenol compound in an organic solvent. The reaction temperature is 70 to 180°C and the reaction time is 0.5 to 6 hours. The maleimide-modified resin after prepolymerization has better heat resistance and bending strength, and the curing conditions of the maleimide resin are reduced, so that the processability is better. The resin composition prepared by the invention is used to make a prepreg and a laminate. The laminate has good comprehensive properties such as good heat resistance, peeling strength, low dielectric property, bending resistance, low thermal expansion coefficient and the like, and can be used in the field of packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and in particular to a resin composition and a prepreg and a laminate made using the same. Background Art

[0002] With the rapid development of electronic circuit boards, the high density and high integration requirements of the wiring density of printed circuit boards are becoming more and more stringent. Therefore, it is difficult for traditional epoxy resins to meet the high requirements of laminates (also known as copper clad laminates (CCL)) in terms of heat resistance, mechanical properties, processability, dielectric properties, etc., especially the thermal expansion coefficient. The thermal expansion coefficient of the laminates obtained is required to be lower and lower. In summary, polybismaleimide resins with excellent heat resistance and low thermal expansion coefficient are widely used in high-density installation and high-layer laminates. Although its heat resistance is very excellent, it has high hygroscopicity and problems in adhesion. Furthermore, it requires a higher temperature and longer time than epoxy resins during lamination, and has disadvantages such as poor productivity.

[0003] That is, generally speaking, in the case of epoxy resin, curing can be performed at a temperature of 180° C. or less, but in the case of laminating polybismaleimide resin, a high temperature of 220° C. or more and a long treatment are required. In addition, since the modified imide resin is modified with a low molecular weight compound containing a hydroxyl group and an epoxy group in order to ensure solubility in a general solvent such as propylene glycol monomethyl ether, the heat resistance of the obtained modified imide resin is greatly reduced compared to the polybismaleimide resin. The prior art discloses a reaction prepolymer of maleimide resin and amino silicone. For example, the prior art CN115449039A discloses a modified bismaleimide prepolymer, a resin composition and an application of the resin composition, which are prepared by reacting a bismaleimide compound, a double-bond silicone resin and a hydrocarbon resin; the prior art CN115806737A discloses a resin composition and a product thereof, which comprises 100 parts by weight of a prepolymer and 100 to 250 parts by weight of deflagration-processed spherical silica, wherein: the prepolymer is prepared by a prepolymerization reaction of a reaction mixture; the prior art can improve the brittleness problem of maleimide resin to a certain extent and reduce CTE, but there are still problems such as poor heat resistance, weak bending resistance, and poor material processability.

[0004] Therefore, in order to solve the above problems, the present invention provides a resin composition and a semi-cured sheet and a laminate made using the same, so as to improve the comprehensive properties of the modified maleimide prepolymer when used in the laminate, such as heat resistance, peel strength, low dielectric properties, bending resistance, and low thermal expansion coefficient. Summary of the invention

[0005] The purpose of the present invention is to provide a resin composition and a semi-cured sheet and a laminate made using the same, so as to improve the comprehensive properties of the modified maleimide prepolymer when applied to the laminate, such as heat resistance, peel strength, low dielectric properties, bending resistance, and low thermal expansion coefficient.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A resin composition, comprising the following components in parts by weight:

[0008] (A) prepolymer: 80 to 150 parts by weight;

[0009] (B) thermosetting resin: 5 to 100 parts by weight;

[0010] (C) inorganic filler: 10 to 400 parts by weight;

[0011] The prepolymer is obtained by reacting maleimide resin, difunctional vinylbenzene compound, amino-modified silicone oil and aminophenol compound in an organic solvent.

[0012] Preferably, in parts by weight, the maleimide resin is 30 to 70 parts by weight, the difunctional vinylbenzene compound is 5 to 25 parts by weight, the amino-modified silicone oil is 10 to 50 parts by weight, the aminophenol compound is 1 to 10 parts by weight, the reaction temperature is 70°C to 180°C, and the reaction time is 0.5 hour to 6 hours.

[0013] Preferably, the maleimide resin is at least one of the following structures:

[0014]

[0015] Wherein, R2 is hydrogen, methyl or ethyl, R1 is methylene, ethylene or

[0016]

[0017] n is an integer from 1 to 10;

[0018] n is an integer from 1 to 10;

[0019] n is an integer from 1 to 10;

[0020] n is an integer from 1 to 10;

[0021] R is hydrogen, methyl or ethyl, and n is an integer of 1-10.

[0022] For example, the maleimide resin is selected from BMI, BMI-70, BMI-80, BMI-50P, etc. of KI Chemical, or BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2300, BMI-3000, BMI-3000H, BMI-4000, BMI-5100, BMI-7000, BMI-7000H, BMI-TMH, etc. produced by Daiwakasei Industry, or DFE930, DFE936, DFE950, etc. produced by Sichuan Dongcai Technology.

[0023] Preferably, the difunctional vinylbenzene compound contains at least one of the following structures:

[0024]

[0025] Among them, the R group is -CH2-, -CH2-CH2-, -O-,

[0026] More preferably, the difunctional vinylbenzene compound has an R group of -CH2-CH2-.

[0027] More preferably, the difunctional vinylbenzene compound contains at least a nitrogen atom.

[0028] When the difunctional vinylbenzene compound contains nitrogen atoms, the vinylbenzene compound and maleimide can be better copolymerized through the alternating copolymerization of the charge transfer complex, which makes the two more easily reacted and reduces the difficulty of curing of maleic anhydride.

[0029] Preferably, the amino-modified silicone oil comprises a compound represented by the following structural formula:

[0030]

[0031] Here, R1 each independently represents an alkylene group having 1 to 20 carbon atoms, and n is an integer of 0 to 20.

[0032] Preferably, the amino-modified silicone oil is selected from any one or more of the following grades:

[0033] At least one of X-22-161A, X-22-161B, KF-8012 or X-22-1660B-3 manufactured by Shin-Etsu Chemical.

[0034] In the above technical solution, the aminophenol compound is p-aminophenol.

[0035] Preferably, the p-aminophenol is represented by the following structure:

[0036]

[0037] Preferably, the thermosetting resin is selected from at least one of epoxy resin, cyanate resin, polyphenylene ether resin, benzoxazine resin, hydrocarbon resin or active ester resin.

[0038] Preferably, the cyanate resin is selected from at least one of bisphenol A cyanate resin, bisphenol E cyanate resin, bisphenol F cyanate resin, bisphenol M cyanate resin, biphenyl cyanate resin and naphthalene cyanate resin.

[0039] Preferably, the epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, naphthalene ring epoxy resin, dicyclopentadiene epoxy resin, isocyanate epoxy resin, aralkyl linear novolac epoxy resin, alicyclic epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, and glycidyl ester epoxy resin.

[0040] Further preferably, the epoxy resin is selected from at least one of the following structures:

[0041]

[0042]

[0043] Preferably, the polyphenylene ether resin is selected from at least one of ethylene-modified polyphenylene ether resin, methacrylate-modified polyphenylene ether resin, allyl-modified polyphenylene ether resin and hydroxyl-modified polyphenylene ether resin.

[0044] Preferably, the benzoxazine resin is selected from at least one of a DCPD type benzoxazine resin, a bisphenol A type benzoxazine resin, a bisphenol F type benzoxazine resin, a bisphenol M type benzoxazine resin, a biphenyl type benzoxazine resin or an allyl benzoxazine resin.

[0045] Preferably, the hydrocarbon resin is at least one selected from polybutadiene, polystyrene, butadiene-styrene copolymer, butadiene-divinylbenzene-styrene copolymer, butadiene-divinylbenzene copolymer, divinylbenzene-styrene copolymer and polypentadiene.

[0046] Preferably, the active ester resin is selected from at least one of DCPD type active ester, phenolic type active ester, naphthalene type active ester or double bond-containing active ester.

[0047] More preferably, the thermosetting resin is a composition of 10 to 60 parts by weight of epoxy resin and 10 to 70 parts by weight of cyanate resin.

[0048] Preferably, the inorganic filler comprises one or more of silicon dioxide, aluminum hydroxide, talc, aluminum oxide, magnesium hydroxide, magnesium oxide, and ceramic powder having a particle size distribution D100 value less than or equal to 6.0 microns.

[0049] More preferably, the filler is silicon dioxide.

[0050] More preferably, the filler is surface-treated spherical silica.

[0051] The surface treatment agent is a silane coupling agent, such as a vinyl, aniline, isocyanate, methacrylic, epoxy, or alkyl silane coupling agent.

[0052] More preferably, the filler has a particle size D100 value of 1 to 6 microns, such as 1 micron, 2 microns, 5 microns, or 6 microns. More preferably, the filler has a median particle size value of 1 to 4 microns.

[0053] Furthermore, the resin composition further comprises 0.01 to 5 parts by weight of a catalyst, wherein the catalyst is at least one of an imidazole catalyst, a pyridine catalyst, and an organic metal salt catalyst.

[0054] Preferably, the catalyst is at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octanoate.

[0055] Furthermore, the resin composition further comprises a dispersant and a coupling agent, wherein the content of the dispersant is 0.001 to 5 parts by weight, and the content of the coupling agent is 0.001 to 10 parts by weight.

[0056] Specifically, the dispersant is BYK-161 or / and BYK-111 manufactured by BYK. The coupling agent is KBM-402, KBM-403, KBM-502, KBE-503, KBM-603, KBM-903, KBM-573, KBM-602, KBM-1003, etc. manufactured by Xinyue Chemical.

[0057] Furthermore, the resin composition also includes a flame retardant, and the flame retardant is 1 to 60 parts by weight; the flame retardant can improve the flame retardancy of the final cured product, and the cured product is a prepreg, a laminate, and a printed circuit board.

[0058] Specifically, the flame retardant is at least one selected from bromine flame retardants, phosphorus flame retardants, nitrogen flame retardants, organic silicon flame retardants, organic metal flame retardants, and inorganic flame retardants.

[0059] Wherein, the bromine flame retardant is selected from one or more of decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide. The phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate compounds, phosphonic acid compounds, phosphinic acid compounds, phosphine oxide compounds, 9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, tri(2,6-dimethylphenyl)phosphine, (m is an integer from 1 to 5), One or more of organic phosphorus-containing compounds such as phosphazene. Nitrogen-based flame retardants are selected from one or more of triazine compounds, cyanuric acid compounds, isocyanate compounds, phenothiazines, etc. Organosilicon flame retardants are selected from one or more of silicone oils, silicone rubbers, silicone resins, etc. Organometallic salt flame retardants are selected from one or more of ferrocene, acetylacetone metal complexes, organometallic carbonyl compounds, etc. Inorganic flame retardants are selected from one or more of aluminum hydroxide, magnesium hydroxide, aluminum oxide, barium oxide, etc.

[0060] Specifically, the flame retardant is selected from SPB-100 produced by Otsuka Chemical, FP-100, FP-300B or FP-390 produced by Fushimi Pharmaceutical, PX-200, PX-201 or PX-202 produced by Daihachi Chemical, OP-935 or OP-930 produced by Clariant, SAYTEX8010, HP-7010 or BT-93W produced by Albemarle, OL3001 or OL5000 produced by FRX of the United States, etc.

[0061] The present application also claims protection for a prepreg, which is obtained by adding a solvent to the above resin composition to dissolve it into a glue solution, immersing a reinforcing material in the glue solution, and heating and drying the immersed reinforcing material.

[0062] Specifically, the prepreg comprises a reinforcing material and the above-mentioned resin composition attached to the surface of the reinforcing material.

[0063] The reinforcing material is selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.

[0064] Preferably, the reinforcing material is glass fiber cloth, and the glass fiber cloth is surface treated with a silane coupling agent; the glass fiber cloth is preferably open fiber cloth or flat cloth; more preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth or Q glass fiber cloth; the silane coupling agent is preferably an epoxy silane coupling agent or an amino silane coupling agent, etc., to provide good water resistance and heat resistance.

[0065] The preparation method of the prepreg is as follows:

[0066] Preparation of prepolymer: maleimide resin is added into a closed stirring reaction vessel filled with propylene glycol monomethyl ether (PM for short), heated to 105-110°C and stirred for 15-20 minutes to dissolve the maleimide resin, then amino-modified silicone oil, difunctional vinylbenzene compound and aminophenol compound are added dropwise, heated to 115-120°C and stirred for 2-2.5 hours to obtain prepolymer;

[0067] Then, the prepolymer, the thermosetting resin and the inorganic filler are dissolved in a solvent to prepare a resin composition glue;

[0068] The reinforcing material is immersed in the above-mentioned resin composition glue solution, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.

[0069] In a specific embodiment, the impregnated reinforcing material is baked at 100° C. to 180° C. for 1 min to 15 min, and the prepreg is obtained after drying.

[0070] Preferably, the solvent can be selected from one or a combination of acetone, butanone, toluene, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0071] The amount of the solvent used in the present invention is not specifically limited, and the amount of the solvent used is selected by those skilled in the art based on their own experience, as long as the obtained resin composition glue can reach a viscosity suitable for use.

[0072] The present application also claims a laminated board, which can be obtained by coating metal foil on one or both sides of at least one of the above-mentioned prepregs and hot pressing them into shape.

[0073] The laminate includes at least one of the above-mentioned prepregs and a metal foil formed on at least one side of the prepreg.

[0074] In an embodiment where the laminate includes at least two of the above-mentioned semi-cured sheets, the at least two semi-cured sheets are stacked and bonded together by heating and pressurizing, and then metal foil is bonded on one side or both sides of the bonded semi-cured sheets by heating and pressurizing to form the laminate.

[0075] Specifically, the preparation steps of the laminate are as follows: a metal foil is coated on one or both sides of the above-mentioned semi-cured sheet, or at least two of the above-mentioned semi-cured sheets are stacked, and then coated on one or both sides with metal foil, and hot-pressed to obtain a laminate.

[0076] The pressing conditions of the above laminated board are: pressing at a pressure of 0.2 to 2 MPa and a temperature of 150° C. to 250° C. for 1.5 to 4 hours.

[0077] The number of the prepreg sheets can be determined according to the required thickness of the laminate, and one or more sheets can be used.

[0078] The metal foil may be copper foil or aluminum foil, and its material is not limited; the thickness of the metal foil is not particularly limited, such as 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.

[0079] Working mechanism of the present invention:

[0080] The invention uses a difunctional vinylbenzene compound to perform prepolymerization with a maleimide resin, an amino-modified silicone oil and p-aminophenol. The difunctional vinylbenzene compound improves the reaction activity and the intermolecular crosslinking density of maleimide, and the double bonds between the molecules also have good dielectric properties. The addition of the amino-modified silicone oil and p-aminophenol further improves the toughness and reaction rate of the prepolymer. The maleimide-modified resin after prepolymerization has more excellent heat resistance and bending strength, and the curing conditions of the maleimide resin are reduced, so the processability is better. The laminated board prepared by combining with a thermosetting resin has good comprehensive properties such as good heat resistance, peeling strength, low dielectric properties, bending resistance, and low thermal expansion coefficient.

[0081] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0082] 1. The present invention uses a difunctional vinylbenzene compound to prepolymerize with a maleimide resin, an amino-modified silicone oil, and p-aminophenol. The difunctional vinylbenzene compound improves the reactivity and intermolecular crosslinking density of maleimide, and the double bonds between molecules also have good dielectric properties. The addition of amino-modified silicone oil and p-aminophenol further improves the toughness and reaction rate of the prepolymer. The maleimide-modified resin after prepolymerization has better heat resistance and bending strength, and at the same time reduces the curing conditions of the maleimide resin, and has better processability.

[0083] 2. The laminate produced by the present invention has good comprehensive properties such as good heat resistance, peel strength, low dielectric properties, bending resistance, low thermal expansion coefficient, etc., and can be used in the packaging field. DETAILED DESCRIPTION

[0084] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.

[0085] The present invention is further described below in conjunction with the examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0086] Synthesis Example 1: Preparation of prepolymer

[0087] A prepolymer was prepared according to the components and contents in Table 1. The maleimide resin was added to a closed stirring reaction vessel containing propylene glycol monomethyl ether (PM for short). The temperature was raised to 110° C. and stirred for 15 minutes to dissolve the maleimide resin. Then, amino-modified silicone oil, a difunctional vinylbenzene compound and an aminophenol compound were added dropwise. The temperature was raised to 120° C. and the stirring reaction was continued for 2 hours to obtain a prepolymer.

[0088] Example 1

[0089] This embodiment is a resin composition, which includes, by weight: 60 parts of maleimide resin BMI-70, 20 parts of amino-modified silicone oil X-22-161A, 5 parts of p-aminophenol, 10 parts of N-DVBP, 20 parts of PN type cyanate, and 200 parts of silicon dioxide.

[0090] Example 2

[0091] This embodiment is a resin composition, which includes, by weight: 65 parts of maleimide resin BMI-70, 20 parts of amino-modified silicone oil X-22-161B, 5 parts of p-aminophenol, 15 parts of N-DVBP, 25 parts of polyphenylene ether resin, and 200 parts of silicon dioxide.

[0092] Example 3

[0093] This embodiment is a resin composition, which includes, by weight: 70 parts of maleimide resin BMI-80, 30 parts of amino-modified silicone oil X-22-161A, 5 parts of p-aminophenol, 10 parts of BVPE, 20 parts of PN type cyanate ester, and 200 parts of silicon dioxide.

[0094] Example 4

[0095] This embodiment is a resin composition, which includes, by weight: 70 parts of maleimide resin BMI-80, 20 parts of amino-modified silicone oil X-22-161B, 5 parts of p-aminophenol, 10 parts of BVPE, 10 parts of bisphenol A novolac epoxy resin, 20 parts of PN type cyanate ester, and 200 parts of silica.

[0096] Example 5

[0097] This embodiment is a resin composition, which includes, by weight: 60 parts of maleimide resin BMI-70, 20 parts of amino-modified silicone oil X-22-161A, 5 parts of p-aminophenol, 10 parts of N-DVBP, 10 parts of BVPE, 20 parts of PN type cyanate, and 200 parts of silicon dioxide.

[0098] Comparative Example 1

[0099] This embodiment is a resin composition, which includes, by weight: 60 parts of maleimide resin BMI-70, 20 parts of amino-modified silicone oil X-22-161A, 5 parts of p-aminophenol, 20 parts of PN type cyanate, and 200 parts of silicon dioxide.

[0100] Comparative Example 2

[0101] This embodiment is a resin composition, which includes, by weight: 65 parts of maleimide resin BMI-70, 20 parts of amino-modified silicone oil X-22-161B, 5 parts of p-aminophenol, 25 parts of polyphenylene ether resin, and 200 parts of silicon dioxide.

[0102] Comparative Example 3

[0103] This embodiment is a resin composition, which includes, by weight: 70 parts of maleimide resin BMI-80, 30 parts of amino-modified silicone oil X-22-161A, 5 parts of p-aminophenol, 20 parts of PN type cyanate, and 200 parts of silicon dioxide.

[0104] The components and addition amounts of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1 below.

[0105] Table 1

[0106]

[0107] The raw material manufacturers and models of each component used in Examples 1-5 and Comparative Examples 1-3 are shown in Table 2 below.

[0108] Table 2

[0109]

[0110] Synthesis of N-DVBP: 46.5 g (0.5 mol) of aniline, 152.5 g (1.0 mol) of CMSAM and 10 g (1.0 mol) of phase transfer catalyst (butylammonium bromide) were dissolved in toluene, and then 160 g of an aqueous solution of sodium hydroxide was added under stirring, the temperature was raised to 90±2°C, and stirring was continued for 5 hours; after the reaction was completed, the toluene layer was separated and repeatedly washed with water until the pH value became 7, and finally toluene was distilled under reduced pressure to obtain N,N'-divinylbenzylaniline.

[0111] Mixing of glue:

[0112] According to the formula in Table 1, all the components in the formula are prepared into a thermosetting resin composition glue solution with a solid content of 60%; the reinforcing material is immersed in the above resin composition glue solution, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg;

[0113] A laminated board can be obtained by coating one or both sides of the above-mentioned prepreg with metal foil, or by stacking at least two of the above-mentioned prepregs and then coating one or both sides with metal foil, and then hot pressing. Specifically, the laminated board can be obtained under the following conditions:

[0114] Reinforcement material: ordinary electronic grade 2116 glass fiber cloth;

[0115] Metal foil: 18 microns, electrolytic copper foil;

[0116] Number of layers: 6;

[0117] Thickness of sheet after forming: 0.6mm;

[0118] Pre-impregnation semi-curing conditions: 170℃ / 5min;

[0119] Curing conditions: 150℃ / 60min+220℃ / 100min(150min).

[0120] The resin compositions prepared in Examples 1-5 and Comparative Examples 1-3 were used to make laminates for testing. The test results of various properties are shown in Table 3 below.

[0121] Table 3

[0122]

[0123] The test methods for each performance in the table are as follows:

[0124] (1) Glass transition temperature was measured by DMA (thermomechanical analysis) at a heating rate of 10°C / min;

[0125] (2) Peel strength: Test the peel strength of the metal cover layer according to the "after thermal stress" experimental conditions in IPC-TM-6502.4.8 method;

[0126] (3) Tin immersion heat resistance: Use a 50×50mm double-sided copper sample, immerse it in 288℃ solder, and record the time it takes for the sample to delaminate and bubble;

[0127] (4) Solder heat resistance: A 5 cm copper-clad laminate was prepared and the evaluation substrate was floated in a solder bath at 288°C for 1 minute. The appearance was then observed to evaluate the solder heat resistance.

[0128] (5) Water absorption: measured according to the method of IPC-TM-6502.6.2.1;

[0129] (6) X / Y thermal expansion coefficient (CTE) determination: TMA (thermomechanical analysis) was used, with a heating rate of 10°C / min and a test temperature range of 30 to 100°C;

[0130] (7) Young's modulus (50°C / GPa): TMA (thermomechanical analysis) was used with a heating rate of 10°C / min and a test temperature range of 30 to 260°C.

[0131] (8) Dk and Df: measured at 10 GHz using the Split Dielectric Resonator (SPDR) method as specified in IPC-TM-6502.5.5.13;

[0132] (9) Appearance quality: Visually inspect the appearance of the CCL substrate. The substrate without obvious glue deficiency or pinholes has a good appearance, while the substrate with glue deficiency or pinholes has a fair appearance.

[0133] (10) T300 copper strip: TMA (thermomechanical analysis) was used with a heating rate of 10°C / min and a test temperature range of 30 to 350°C.

[0134] As can be seen from the above table, the pressed board of the embodiment has significantly better Tg (DMA), heat resistance and X / YCTE than the comparative example, and the board is easier to cure.

[0135] In summary, the resin composition of the present invention has good comprehensive properties such as heat resistance, peel strength, and low thermal expansion coefficient, and can be used in packaging applications, and has better processability and lower curing requirements.

[0136] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A resin composition, characterized in that By weight, it includes the following components: (A) prepolymer: 80 to 150 parts by weight; (B) thermosetting resin: 5 to 100 parts by weight; (C) inorganic filler: 10 to 400 parts by weight; The prepolymer is obtained by reacting maleimide resin, difunctional vinylbenzene compound, amino-modified silicone oil and aminophenol compound in an organic solvent.

2. The resin composition according to claim 1, characterized in that In parts by weight, the maleimide resin is 30 to 70 parts by weight, the difunctional vinylbenzene compound is 5 to 25 parts by weight, the amino-modified silicone oil is 10 to 50 parts by weight, and the aminophenol compound is 1 to 10 parts by weight. The reaction temperature of the reaction is 70° C. to 180° C., and the reaction time is 0.5 hour to 6 hours.

3. The resin composition according to claim 1, characterized in that The maleimide resin is at least one of the following structures: Wherein, R2 is hydrogen, methyl or ethyl, R1 is methylene, ethylene or n is an integer from 1 to 10; n is an integer from 1 to 10; n is an integer from 1 to 10; n is an integer from 1 to 10; R is hydrogen, methyl or ethyl, and n is an integer of 1-10.

4. The resin composition according to claim 1, characterized in that The difunctional vinylbenzene compound contains at least one of the following structures: Among them, the R group is -CH2-, -CH2-CH2-, -o-, 5. The resin composition according to claim 4, characterized in that The difunctional vinylbenzene compound contains at least a nitrogen atom.

6. The resin composition according to claim 1, characterized in that The amino-modified silicone oil includes a compound shown in the following structural formula: Here, R1 each independently represents an alkylene group having 1 to 20 carbon atoms, and n is an integer of 0 to 20.

7. The resin composition according to claim 1, characterized in that The thermosetting resin is selected from at least one of epoxy resin, cyanate resin, polyphenylene ether resin, benzoxazine resin, hydrocarbon resin or active ester resin.

8. The resin composition according to claim 1, characterized in that The inorganic filler comprises one or more of silicon dioxide, aluminum hydroxide, talcum powder, aluminum oxide, magnesium hydroxide, magnesium oxide, and ceramic powder, the particle size distribution D100 of which is less than or equal to 6.0 microns.

9. A prepreg, characterized in that: The prepreg sheet can be obtained by adding a solvent to the resin composition as claimed in any one of claims 1 to 8 to dissolve it into a glue solution, immersing the reinforcing material in the glue solution, and heating and drying the immersed reinforcing material.

10. A laminated board, characterized in that: The laminated board can be obtained by coating metal foil on one or both sides of at least one prepreg as claimed in claim 9 and hot pressing the prepreg.

Citation Information

Patent Citations

  • Modified bismaleimide prepolymer, resin composition and application of resin composition

    CN115449039A

  • Resin composition and product thereof

    CN115806737A